2004
DOI: 10.1021/bm0345256
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Environment for Immobilized Dehydrogenase Enzymes by Modifying Nafion with Tetraalkylammonium Bromides

Abstract: Recent research in our group has shown that mixture-casting Nafion with quaternary ammonium bromides can increase the electrochemical flux of redox couples through the membrane and allow for larger redox species to diffuse to the electrode surface. The research has also suggested that when these salts are cast with Nafion micellar pore size is changing. Therefore, it was proposed that the quaternary ammonium salts could be employed to tailor the structure of the Nafion membrane for immobilizing enzymes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 194 publications
(135 citation statements)
references
References 31 publications
3
130
0
1
Order By: Relevance
“…51 TBAB modified Nafion has previously been shown to provide stabilizing properties when immobilizing enzymes, while allowing ion conductivity. 52 Polyamines, specifically poly-ethylenimines (PEI), are a group of polymers that have been shown to cross-link in the presence of biological surfaces, which can assist in stabilization and/or immobilization of biomolecules on surfaces. 53 Branched PEIs have been shown to adsorb onto the surface of CNTs.…”
mentioning
confidence: 99%
“…51 TBAB modified Nafion has previously been shown to provide stabilizing properties when immobilizing enzymes, while allowing ion conductivity. 52 Polyamines, specifically poly-ethylenimines (PEI), are a group of polymers that have been shown to cross-link in the presence of biological surfaces, which can assist in stabilization and/or immobilization of biomolecules on surfaces. 53 Branched PEIs have been shown to adsorb onto the surface of CNTs.…”
mentioning
confidence: 99%
“…Because our enzymatic system involves a variety of dehydrogenases, TBAB was the quaternary ammonium bromide salt employed in modifying the Nafion membrane as previous research has shown that it is ideal for immobilization of the majority of dehydrogenases. [9][10][11] The TBAB-modified Nafion membrane was formed in a two-step process. The first step was to cast a suspension of Nafion with TBAB dissolved in suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Nafion is currently the archetype material for and lactic dehydrogenases) in a tetraalkylammonium bromide modified Nafion membrane. 10,11 Although Nafion is capable of immobilizing a variety of enzymes, it is expensive and is lacks biocompatibility and biodegradability. 5 Chitosan is, therefore, an ideal alternative to Nafion as it is less expensive, biodegradable and has better biocompatibility.…”
Section: General Overviewmentioning
confidence: 99%